Incidence and risk factors of anaesthesia-related perioperative cardiac arrest: A 6-year observational study from a tertiary care university hospital. Issue 4 (April 2018) - Hohn, Andreas; Machatschek, Jan-Nicolas; Franklin, Jeremy; Padosch, Stephan A.
Abstract : BACKGROUND: In recent decades, the incidences of anaesthesia-related perioperative mortality and adverse outcomes have decreased drastically. However, to date, data on perioperative cardiac arrest and risk factors of perioperative cardiac arrest from European countries are scarce. OBJECTIVES: To determine the incidences of perioperative cardiac arrest and rates of anaesthesia-related and anaesthesia-contributory cardiac arrest. Identification of pre-existing risk factors leading to perioperative cardiac arrest. DESIGN: Retrospective cohort study. SETTING: Department of Anaesthesiology and Intensive Care Medicine, University Hospital of Cologne, Germany. INTERVENTIONS: Perioperative critical incident reports between 2007 and 2012 were screened, and reports on cardiac arrest within 24 h postoperatively were identified. Cardiac arrests were classified as 'anaesthesia-related', 'anaesthesia-contributory' or 'anaesthesia-unrelated' by two reviewers independently. Univariate and multi-variate logistic regression analysis was used to identify risk factors associated with perioperative cardiac arrest. RESULTS: Analysis of 318 critical incidents from 169 500 anaesthetics revealed 99 perioperative cardiac arrests. This is an overall incidence of perioperative cardiac arrest of 5.8/10 000 anaesthetics [95% confidence interval (CI), 4.7 to 7.0]. The rate of anaesthesia-related cardiac arrest was 0.7/10 000 (95% CI, 0.3 to 1.1), and the rate of anaesthesia-contributory cardiac arrest was 1.7/10 000 (95% CI, 1.1 to 2.3). Most cardiac arrests related to anaesthesia were due to respiratory events. From the multi-variate analysis, American Society of Anesthesiologists physical status grade at least 3 [ P  = 0.007, odds ratio (OR) 2.59 (95% CI, 1.29 to 5.19)], emergency surgery [ P   <  0.001, OR 4.00 (95% CI, 2.15 to 7.54)] and pre-existing cardiomyopathy [ P  < 0.001, OR 17.48 (95% CI, 6.18 to 51.51)] emerged as predictors of cardiac arrest. CONCLUSION: These first available European data on perioperative cardiac arrest from a large unselected cohort indicate that the overall perioperative incidence of cardiac arrest at our institution was slightly lower than published in the literature, whereas rates of anaesthesia-related and anaesthesia-contributory cardiac arrest were comparable. Most cardiac arrests related to anaesthesia were due to respiratory events. American Society of Anesthesiologists physical status grade at least 3, emergency surgery and pre-existing cardiomyopathy appear to be relevant risk factors for cardiac arrest. Abstract : Supplemental Digital Content is available in the text